Inside Cover Image, Volume 31, Issue 11. (19th October 2018) - Vareth, Maryam; Lupo, Janine; Larson, Peder; Nelson, Sarah
Abstract : The cover image, by is based on the Research Article A comparison of coil combination strategies in 3D multi‐channel MRSI reconstruction for patients with brain tumors by Maryam Vareth et al., https://doi.org/10.1002/nbm.3929 .